Network attention and carbon dioxide emission performance of agricultural enterprises: Empirical evidence from China’s baidu search index - Chen, Jiancheng; Sun, Heng (Frontiers in Environmental Science, 2023)
Based on the network attention data of China's agricultural listed companies from 2012 to 2020, this paper uses the IV model to measure and investigate the impact of network attention on the carbon dioxide emission performance of China's agricultural listed companies and its mechanism. The findings are as follows: (1) The carbon dioxide emission intensity of listed agricultural companies in China is generally decreasing year by year and the carbon dioxide emission performance is improving; (2) The increasing network attention has significantly reduced the carbon dioxide emission intensity of agricultural listed companies and brought about better carbon dioxide emission performance; (3) The relationship between network attention and carbon dioxide emission performance of agricultural listed companies has network, regional and property heterogeneity; (4) The investment in environmental protection has strengthened the inhibition effect of network attention on the unit carbon dioxide emissions of agricultural listed companies. The research conclusion enriches the literature on "network concern - environmental governance", and also provides ideas for developing countries to exert the environmental governance effect of network concern in the process of carbon neutrality.